2019
DOI: 10.1213/ane.0000000000003821
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Pediatric Perioperative Surgical Home Integrated Care Coordination Pathway for Laryngeal Cleft Repair

Abstract: BACKGROUND: The Pediatric Perioperative Surgical Home (PPSH) model is an integrative care model designed to provide better patient care and value by shifting focus from the patient encounter level to the overarching surgical episode of care. So far, no PPSH model has targeted a complex airway disorder. It was hypothesized that the development of a PPSH for laryngeal cleft repair would reduce the high rates of postoperative resource utilization observed in this population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Previous studies have shown significant cost reduction ($169 per episode) in adult patients undergoing total hip or knee arthroplasty 18 . As healthcare institutions move toward bundled payment models for procedures, they are more likely to benefit from perioperative surgical home programs as they reduce ICU utilization and overall length of stay 4,5,7 . Costs of care in the operating room range from $37 to $150 per minute 19‐22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown significant cost reduction ($169 per episode) in adult patients undergoing total hip or knee arthroplasty 18 . As healthcare institutions move toward bundled payment models for procedures, they are more likely to benefit from perioperative surgical home programs as they reduce ICU utilization and overall length of stay 4,5,7 . Costs of care in the operating room range from $37 to $150 per minute 19‐22 .…”
Section: Discussionmentioning
confidence: 99%
“…18 As healthcare institutions move toward bundled payment models for procedures, they are more likely to benefit from perioperative surgical home programs as they reduce ICU utilization and overall length of stay. 4,5,7 Costs of care in the operating room range from $37 to $150 per minute. [19][20][21][22] If the preanesthetic evaluation of pediatric patients does not begin until the patient arrives on their day of surgery, then there is a greater likelihood that new findings by patient history may (appropriately) require lengthier investigation or same-day consultations and diagnostic testing.…”
Section: F I G U R E 3 Same Day Case Cancellations For Pediatric Cases Requiring Anesthesia By (A) Cancellation Reason and (B) Age Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline patient characteristics were collected including insurance (private or public payer) and procedure type (total hip, knee, shoulder, and unilateral knee arthroplasty aka THA, TKA, TSA, and UKA, respectively). These characteristics have shown to be closely associated with surgical outcome risks (Alvis et al, 2017;Kim et al, 2019;Leahy et al, 2019). Additionally, residence (zip code) was also collected to assess differences in surgical outcomes between patients residing in same county as the hospital and patients residing elsewhere.…”
Section: Methodsmentioning
confidence: 99%